2016
DOI: 10.1186/s13014-016-0649-z
|View full text |Cite
|
Sign up to set email alerts
|

The dosimetric impact of implants on the spinal cord dose during stereotactic body radiotherapy

Abstract: BackgroundThe effects of spinal implants on dose distribution have been studied for conformal treatment plans. However, the dosimetric impact of spinal implants in stereotactic body radiotherapy (SBRT) treatments has not been studied in spatial orientation. In this study we evaluated the effect of spinal implants placed in sawbone vertebra models implanted as in vivo instrumentations.MethodsFour different spinal implant reconstruction techniques were performed using the standard sawbone lumbar vertebrae model;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Cobalt chrome causes significant beam scatter thus altering the dose delivered to the tumor and organs at risk whereas titanium has been shown to cause minimal radiation beam scatter. 100,101 Carbon fiber implants may provide a superior stabilization option for patients with planned postoperative proton beam therapy treatment, since the presence of metallic implants has been shown to have a detrimental effect on local tumor control after proton therapy. 102,103 Implants based on from carbon fiber also offer superior MR image quality, which may be beneficial for long-term surveillance/monitoring of local tumor control.…”
Section: Treatment Techniquesmentioning
confidence: 99%
“…Cobalt chrome causes significant beam scatter thus altering the dose delivered to the tumor and organs at risk whereas titanium has been shown to cause minimal radiation beam scatter. 100,101 Carbon fiber implants may provide a superior stabilization option for patients with planned postoperative proton beam therapy treatment, since the presence of metallic implants has been shown to have a detrimental effect on local tumor control after proton therapy. 102,103 Implants based on from carbon fiber also offer superior MR image quality, which may be beneficial for long-term surveillance/monitoring of local tumor control.…”
Section: Treatment Techniquesmentioning
confidence: 99%
“…Furthermore, the spinal implants cause backscattering of electrons increasing the dose in front of the material while limiting the dose behind the spinal implants [8]. Yazici et al [26] demonstrated that the dose to the spinal cord increased up to 18.6% when spinal implants were present in the SBRT treatment field. Avoiding interaction between the radiation beam and the spinal implant to prevent high doses to the spinal cord is therefore important but also complicates post-operative SBRT planning [26].…”
Section: Discussionmentioning
confidence: 99%
“…Yazici et al [26] demonstrated that the dose to the spinal cord increased up to 18.6% when spinal implants were present in the SBRT treatment field. Avoiding interaction between the radiation beam and the spinal implant to prevent high doses to the spinal cord is therefore important but also complicates post-operative SBRT planning [26]. Reversing the order of surgery and SBRT may overcome these technical challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional external beam radiation therapy (EBRT) to the entire spine has been the golden standard for decades due to its excellent palliative effect. However, EBRT doses are too low to ensure long term local control, and raising the dose is not an option because the spinal cord is often at risk 8 . Fortunately, stereotactic ablative radiotherapy (SABR) is an emerging noninvasive approach for the treatment of spinal OMD 9 .…”
Section: Introductionmentioning
confidence: 99%